Nailbiter. Volume 6, The bloody truth - Williamson, Joshua; Williamson, Joshua; Henderson, Mike, 1981- (Nailbiter, 2017)
Sixteen of the world's worst serial killers were all born and raised in the same small town. For years people have tried to solve the mystery of "Why this town?" And now the truth is finally revealed... but at what cost? The bloody tale of horror from creators JOSHUA WILLIAMSON and MIKE HENDERSON continues! Fans of Wytches, Outcast and The Walking Dead will enjoy this thriller drama!